PENGEMBANGAN BAHAN AJAR NAHWU BERBASIS MIND MAPPING MENGGUNAKAN MEDIA FLIPBOOK DIGITAL - Reno Ryan Saputra; Tarmizi, Ahmad; Nurani, Qoim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop and test the effectiveness of digital Nahwu teaching materials based on Mind Mapping using Flipbooks at MAS Paradigma Palembang. The background of the study is the low level of student understanding regarding Arabic grammatical rules, caused by the use of static conventional media and limited learning time. The method used is Research and Development (R&D) with the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). The research subjects consisted of 20 students from Grade XII at MAS Paradigma Palembang using a saturated sampling technique. Data collection instruments included observation, interviews, questionnaires, and tests. Material validation results showed a percentage of 93.3% (Very Valid), while media validation obtained a score of 73% (Quite Valid), which was subsequently refined through revisions. Implementation results showed an increase in students' average scores from 25.53 on the pre-test to 50.79 on the post-test. Statistical analysis using the Paired Sample T-Test produced a significance value of 0.000 (p < 0.05), proving a significant influence on student learning outcomes. The average N-Gain value of 0.3354 places the product's effectiveness in the moderate category. The conclusion of this study is that Mind Mapping-based Nahwu teaching materials in Flipbook format are highly feasible and effective for use as enrichment media to enhance students' grammatical understanding independently and interactively.